Endoscopy-assisted surgical management for a giant axillary cystic lymphangioma: a case report - Chen, Hai-wei; Li, Rong-jiang; Niu, Yan-bang; Lu, Xiong (Frontiers in Surgery, 2025)
A cystic lymphangioma is a benign malformation that arises from aberrant lymphatic development and commonly occurs in the neck and axilla. While typically asymptomatic, complete surgical excision remains the primary treatment. We present a case of a giant, left axillary cystic lymphangioma (approximately 15 cm × 15 cm × 10 cm) in a young female patient. The following endoscopy-assisted surgical approach was employed: a small incision facilitated initial access and establishment of the operative field, while endoscopy provided magnified visualization of the anatomical relationships between the mass and surrounding structures, enabling precise dissection and complete resection. Histopathological examination confirmed the mass to be a cystic lymphangioma. At the 6-month follow-up, the patient exhibited no complications or recurrence. No reports exist on endoscopic management. The successful management of a cystic lymphangioma in this case offers a valuable reference for the clinical treatment of similar lesions.